1000-fold enhancement in proton conductivity of a MOF using post-synthetically anchored proton transporters - Shalini, Sorout; Dhavale, Vishal M.; Eldho, Kavalakal Mathai; Kurungot, Sreekumar; Ajithkumar, Thalasseril G.; Vaidhyanathan, Ramanathan (Scientific Reports, 2016)
Pyridinol, a coordinating zwitter-ionic species serves as stoichiometrically loadable and non-leachable proton carrier. The partial replacement of the pyridinol by stronger hydrogen bonding, coordinating guest, ethylene glycol (EG), offers 1000-fold enhancement in conductivity (10(-6) to 10(-3) Scm(-1)) with record low activation energy (0.11 eV). Atomic modeling coupled with C-13-SSNMR provides insights into the potential proton conduction pathway functionalized with post-synthetically anchored dynamic proton transporting EG moieties.